Biogeochemical formation of metalliferous laminations in surficial environments. (28th February 2021) - Henne, Anicia; Craw, Dave; Hamilton, Jessica; Paz, Anat; Kerr, Gemma; Paterson, David; Shuster, Jeremiah; Southam, Gordon
Abstract: Finely laminated (cm–μm scale) metalliferous precipitates are widespread in the surficial environment, especially around mineral deposits and reflect biogeochemical processes that can pervade near-surface environments on a larger scale. Examples in this paper involve precipitates of the transition metals Fe, Cu and Mn with minor Co, Ni, V and Zn; the metalloids As and Sb; and authigenic Au. Mobility and re-precipitation are driven primarily by geochemical disequilibrium, especially with respect to pH and redox states, that arises from complex interactions between biological processes, geological processes, and variations in the surrounding environment. Different degrees of chemical disequilibrium arise on small spatial scales on time scales of days to millennia. Interactions between biota, waters and rocks in these small near-surface settings affect the biogeochemical environments. Sulfur- and iron-oxidising bacteria are common biogeochemical agents associated with sulfide-bearing lithologies, but localised reductive environments can also develop, leading to gradients in pH and redox state and differential metal mobility. In general, there is commonly a spatial separation of Fe-rich precipitates from those with Cu and Mn, and other transition metals also follow Cu and Mn rather than Fe. Metalloids As and Sb have a strong affinity for Fe under oxidising conditions, but not under more reducing conditions. However, complex biogeochemical parageneses of laminated metalliferous deposits preclude prediction of finer formation details. The textures, mineral species, and metal associations within these deposits are likely to be encountered in all facets of mineral deposit development: initial exploration activity of near-surface locations, mining of shallow portions of orebodies, especially supergene zones, and downstream environmental management with respect to discharging metalliferous waters.